Implementation of a Stack Data Structure for Browsing History Management in the Form of a Chrome Web Browser Extension - Fitra, Muhammad Rizki Andrian; Pratama, Ega; Al Kautsar, Muhammad Zidane; Harahap, Fatimah Asro; Ramadhani, Fanny (CV. Rayyan Dwi Bharata, 2025)
Browsing history is a fundamental feature in modern browsers, yet its management remains inefficient in many implementations. This research develops a Chrome extension utilizing the Stack data structure, leveraging its Last In, First Out (LIFO) principle to store, search, delete, and open browsing history URLs efficiently. The system is designed with Chrome's API to monitor tab activities, store data locally, and provide an interactive user interface. The findings demonstrate that the stack-based approach is more efficient than conventional methods. The system also offers users straightforward features for managing history, including search and individual deletion capabilities.